2018
DOI: 10.1177/0898010118781620
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Mindfulness Intervention for Nurse Managers

Abstract: These findings suggest that mindfulness practices need to be reinforced. Without continuous reinforcement, it may become a self-care practice moved to the bottom of the list of things to be done among the activities of a busy day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 20 publications
1
52
0
7
Order By: Relevance
“…Six papers (Bazarko et al, ; Ceravolo & Raines, ; Cohen‐Katz et al, ; Delaney, ; Norouzinia et al, ; Poulin et al, ) analysed outcomes achieved under the traditional MBSR approach, with a total duration of 8 weeks. The other studies of MBSR used shorter versions, lasting 6 weeks (Dos Santos et al, ; Duarte & Pinto‐Gouveia, ; Montanari et al, ) or 4 weeks (Craigie et al, ; Gauthier et al, ; Hevezi, ; Mackenzie et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six papers (Bazarko et al, ; Ceravolo & Raines, ; Cohen‐Katz et al, ; Delaney, ; Norouzinia et al, ; Poulin et al, ) analysed outcomes achieved under the traditional MBSR approach, with a total duration of 8 weeks. The other studies of MBSR used shorter versions, lasting 6 weeks (Dos Santos et al, ; Duarte & Pinto‐Gouveia, ; Montanari et al, ) or 4 weeks (Craigie et al, ; Gauthier et al, ; Hevezi, ; Mackenzie et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (Craigie et al, ; Dos Santos et al, ; Slatyer et al, ) showed that a brief intervention can be effective, reducing burnout and maintaining the positive outcome for 6 months. However, Cohen‐Katz et al () found that 3 months after an MBSR programme, the changes obtained only persisted in one of the burnout dimensions (EE), whereas Ceravolo and Raines () recorded an increase in the burnout score during the three subsequent months. Gauthier et al () observed a negative relationship between the EE dimension of burnout and MBSR, immediately following the intervention and at the 1‐month follow‐up, a similarly negative relationship for D immediately after the intervention and a positive one for PA. On the other hand, Bazarko et al () measured a stable average score, for all dimensions of burnout, after 2 and 4 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness‐based stress reduction (MBSR) has been widely known and conducted in clinical populations (Kabat‐Zinn, ). However, the effect of mindfulness interventions on burnout is not fully understood (Ceravolo & Raines, ). Specific to nurses' job burnout, further research on developing modified MBSR programme or other mindfulness‐based programmes and exploring their effectiveness is necessary.…”
Section: Implication For Nursing Managementmentioning
confidence: 99%
“…Thirty-one studies included a mindfulness [62,66,69,93,126,133,135,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159] or meditation [87,[160][161][162][163][164][165][166] intervention (most often with the use of mindfulness-based stress reduction (MBSR) as a mindfulness program). Twenty-four studies [63,[70][71][72]86,96,105,151,160,162,[167][168][169][170][171][172][173][174][175]…”
Section: Mindfulness and Relaxationmentioning
confidence: 99%